Redescobrindo uma controvérsia elizabetana: as (re)leituras do amor em traduções brasileiras dos Sonetos de Shakespeare - Silva, Gisele Dionísio da (2004)
The present assignment aims to investigate how the post-structuralist concept of language calls into question and redefines traditional notions relating to sign, text, reading and translation. Based mainly on the discussions brought about by French philosopher Jacques Derrida's deconstruction, this work intends to verify how the demystification of the idea of a stable and transcendent origin allows for a reconsideration of the conventional status attributed to the supposed 'original' text and the translation, in which both are inserted in an endless chain of intertextuality. Supported by the notion of difference as a basic and inevitable part of all human activities and relations, deconstruction sees in translation the status of a text in its own right, different from the 'original', to be carried out by a translator who's no longer mechanical and intelectually limited, but by a person sociohistorically, culturally and ideologically defined by his/her community. In order to detect the translator's authorship responsibility in his/her work – surrounded by interferences arising from his/her subjectivity and the coercions imposed by the context in which he/she lives –, four Portuguese translations of five poems from the Sonnets, written by the English poet and playwright William Shakespeare, will be examined. The lyrical work in question is of extreme interest due to the many controversies which have surrounded it since its publication in 1609, all of which have been invariably silenced by various critics because they refer to Shakespeare's sexuality and integrity as a national cultural property. Moreover, considering the fact that the Sonnets are the focus of very little critical reflexion in the Brazilian literary scenario, it becomes important to investigate whether the piece's sexual implications has played a major role in its timid reception in our territory. The translations selected for analysis are signed by Péricles Eugênio da Silva Ramos, Jerônimo de Aquino, Oscar Mendes and Jorge Wanderley. It is relevant to observe how translators in Brazil have come to terms with the polemic aspects of this poetic sequence, by shaping their texts with certain choices that allow for a vision of their concepts on language, literariness, poetry and translation.